Tackling the water challenges in Indian cities amid COVID-19. Issue 1 (2nd January 2022) - Chattopadhyay, Seemantini
ABSTRACT: Acknowledging the overreaching importance of WHO guidelines of frequent handwashing with soap and water in battling COVID-19, this paper unravels the state of water supply in Indian cities and examines the challenges of conventional water policy and governance assumptions amid the COVID-19 crisis in India. Urban citizens, especially living in the slums, very often need to rush to access the water sources, making social distancing practically impossible. Apart from increasing public investment, this paper argues for rethinking the existing framework of water supply through institutional reforms focusing on decentralisation, community participation, and adoption of integrated water resource management policies.